Chapter The œconomia of iron and steel: Material transformations, manual skills, and technical improvement in early modern Sweden - Jansson, Måns (Datini Studies in Economic History, 2023)
Sweden was a major exporter of iron during the early-modern period, but there was also an important domestic steelmaking. We analyse the Swedish iron and steel trade in a long perspective in a European context. Our approach departs from recent discussions on industrial and scientific developments, in which the spheres of "Hand" and "Mind" are brought together, and where artisanal skills and natural resources are highlighted. We emphasise how the migration of people, and movements of materials and knowledge, influenced a process of gradual change. A key feature was the ongoing interactions between working people and educated savants. Our conclusion points to the perseverance of artisanal skills well into the nineteenth century, but also towards new links between work, technology, and markets.